Microaggressions and philosophy - Freeman, Lauren; Weekes Schroer, Jeanine (Routledge studies in contemporary philosophy, 2020)
"This is one of the first books to offer a comprehensive philosophical treatment of microaggressions. Its aims are to provide an intersectional analysis of microaggressions that cuts across multiple groups and dimensions of oppression and marginalization, and to engage a variety of perspectives that have been sidelined within the discipline of philosophy. The volume gathers a diverse group of contributors: philosophers of color, philosophers with disabilities, philosophers of various nationalities and ethnicities, and philosophers of several genders and gender identities. Their unique frames of analysis articulate both how the concept of microaggressions can be used to clarify and sharpen our understanding of subtler aspects of oppression and how analysis, expansion, and reconceiving the notion of a microaggression can deepen and extend its explanatory power. The essays in the volume are divided into four thematic parts. The essays in Part I seek to defend microaggressions from common critiques and to explain their impact beyond the context of college students. In Part II the contributors set forth a framework for legitimizing microaggressions research that takes into account issues of measurement, scale, and replication. Part III explores the harms of microaggressions. The chapters show how small slights can accumulate to produce significant harm at the macro level, demonstrate how microaggressions contribute to epistemic harm, and establish novel understandings of racial and accent-triggered microaggressions. Finally, Part IV addresses issues of disability and ableism within the context of microaggressions. It includes commentary on transgender athletes, disciplinary techniques for bodily nonconformity, ableist exceptionalism, and deafness. Microaggressions and Philosophy features cutting-edge research on an important topic that will appeal to a wide range of students and scholars across disciplines. It includes perspectives from philosophy of psychology, empirically informed philosophy, feminist philosophy, critical race theory, disability theory, philosophy of language, philosophy of science, and social and political philosophy"-- Provided by publisher.
Keywords: EDI; approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; histoire et politique; hétérosexisme; intersectionnalité; inégalités; micro-agression; philosophie; psychologie; racisme; sciences humaines; sexisme; sofia; systèmes d'oppressions; thématiques; transphobie; violences; études critiques de la race; études critiques du handicap

The Role of Gender and Ethnicity in Perceptions of Rape and Its Aftereffects - Schneider, Lawrence J.; Mori, Lisa T.; Lambert, Paul L.; Wong, Anna O. (Sex Roles : A Journal of Research, 2009)
Caucasian-, Hispanic-, and Asian-American male and female students (n = 764) attending a California (USA) public university reported their perceptions of sexual assault. After reading a rape vignette, participants gave their impressions of the victim; estimated time needed for recovery and treatment; and recommended a sentence for the assailant. Half of the sample received information regarding state sentencing guidelines. Relative to female participants, males perceived the victim as more responsible. Caucasian-American males had stronger reservation about the victim’s judgment. Males were less inclined to assign blame than were females. Ethnicity was the only factor influencing perceptions of recovery. Ethnicity and sentencing guidelines, but not gender, impacted imprisonment decisions. Issues impeding a unified theoretical understanding of perceptions of rape victims were considered.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; californie; cours; discipline; intersectionnalité; perception; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; santé; sciences humaines; sex2283; thématiques; viol; violences; états-unis

Abused women and survivor therapy - Walker, Lenore E. (American Psychological Association, 2006)
Dans ce manuel de traitement de pointe, Lenore E. A. Walker soutient que les psychothérapies traditionnelles pour les victimes de traumatismes ont été insuffisantes pour traiter les femmes maltraitées. Alors que le problème de la violence à l'égard des femmes continue de tourmenter la société, couvrant tous les secteurs démographiques, Walker décrit des modifications essentielles à la pratique traditionnelle qui permettront aux praticiens de travailler plus efficacement avec les femmes victimes de violence. Ces modifications aboutissent à une compilation intégrée des stratégies d'évaluation et d'intervention les plus réussies, appelées « thérapie de survivant ». La thérapie des femmes maltraitées et des survivants discute des principales formes de violence subies par les femmes : viol et agression sexuelle, coups de feu, abus sexuels commis par des thérapeutes et discrimination/harcèlement sexuel sur le lieu de travail. Walker examine les effets du sexe, de la race, de l'ethnicité, de la culture et de l'orientation sexuelle sur chaque forme d'abus ; discute des considérations cliniques et des approches de traitement ; évalue les instruments d'évaluation couramment utilisés ; et analyse les problèmes médico-légaux dans les cas impliquant la violence contre les femmes. Walker soutient que les modèles de traitement réussis doivent tenir compte de l'impact spécifique des diverses formes d'abus, de la réponse psychologique unique de l'individu au monde, de l'impact de la socialisation traditionnelle des femmes et des hommes, et du transfert de thérapeutes et du contre-transfert. Ces considérations peuvent être appliquées au cours d'une thérapie qui cherche à réautonomiser les femmes maltraitées en les aidant à retrouver leur estime de soi, à rétablir des relations saines et à retrouver un sentiment de contrôle et de choix dans leur vie. La thérapie des femmes maltraitées et des survivants aide les praticien.nes nouvellement formé.e.s ainsi que le praticien.ne expérimenté.e à identifier, évaluer et traiter les femmes qui ont été maltraitées physiquement, sexuellement ou psychologiquement.
Keywords: approches et analyses; cours; discipline; intersectionnalité; psychologie; santé; santé mentale; sciences humaines; thématiques; traumatismes; trs3500; violences; violences conjugales; violences sexuelles

The impact of culture and minority status on women's experience of domestic violence - Kasturirangan, Aarati; Krishnan, Sandhya; Riger, Stephanie (Trauma, violence & abuse, 2004)
The influence of culture and ethnic background on women’s experience of domestic violence has been explored in research only recently. Here the authors review research about the impact of culture and minority status in the United States on women’s experience of domestic violence, considering family structure,immigration, acculturation, oppression, and community response. The authors encourage researchers and service providers to acknowledge the effects on women of sociopolitical dynamics, including racism, and to identify specific aspects of culture that are relevant to intimate partner abuse.
Keywords: amériques; approches et analyses; cours; discipline; intersectionnalité; justice sociale; pauvreté; premier cycle; psychologie; racisme; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; systèmes d'oppressions; thématiques; violences; états-unis